Turnover Intention in Relation to Job Stress and Workload Among Male and Female Employees at PT. Matahari Department Store Tbk, Medan - Sianturi, Anggi Derissa Putri; Melinda, Lamtiur; Situmorang, Yosephine Deborah; Sirait, Kharine Tiatira; Hartini, Sri (Journal Of Management Analytical and Solution (JoMAS), 2025)
This study explores the relationship between job stress, workload, and turnover intention among male and female employees at PT. Matahari Department Store Tbk, Medan. Using a quantitative approach, data were collected from 133 employees through validated questionnaires measuring turnover intention, job stress, and workload. The study employed multiple linear regression analysis using SPSS Statistics 25 to examine the influence of the independent variables. The findings reveal that both job stress and workload significantly affect employees’ turnover intention. Job stress has a positive and significant effect with a beta coefficient of 0.511 (p = 0.000), while workload also shows a significant positive effect with a beta coefficient of 0.473 (p = 0.000). The regression model demonstrates a strong explanatory power, with an adjusted R² value of 0.941, indicating that 94% of the variance in turnover intention is explained by job stress and workload. The remaining 6% is attributed to other unmeasured factors. These results underscore the need for organizations to address workplace stressors and manage workloads effectively to reduce employee turnover, especially when considering gender-related experiences in the work environment